Retrospective analysis of potential sex differences in naturally emerging psychiatric comorbidities over time in Turkish children and adolescents with attention deficit/hyperactivity disorder - Sabide Duygu Uygun; Zeynep Toprak-Kosku; Rahime Duygu Temeltürk; Merve Çıkılı-Uytun; Esra Yürümez; Didem Behice Öztop; Tuğba Menteşe-Babayiğit; Gökçe Yağmur Efendi; Birim Günay Kılıç (Middle East Current Psychiatry, 2025)
Abstract Background Attention Deficit Hyperactivity Disorder (ADHD) comorbidity patterns vary by sex and age, necessitating understanding for effective diagnosis and intervention. The aim was to assess the prevalence, timing, and distribution of comorbid psychiatric disorders in a Turkish sample, focusing on potential sex differences. Methods A retrospective study included 322 children with ADHD (aged 6 to 18 years). Data, including Conners’ Parent/Teacher Rating Scales (CP/TRS), were collected from university-based clinical records. Results Females with ADHD had a higher rate of psychiatric comorbidity compared to males (83.5% vs. 62.7%, p < .001). Neurodevelopmental disorders were more prevalent in females (p < .001). All CTRS indexes (ADHD, restless/impulsive, emotional lability, and total), as well as oppositional and hyperactive/impulsive subscale scores, showed mild negative correlations with the timing of the first comorbidity other than neurodevelopmental disorders. Logistic regression identified age and specific learning disorders (SLD) as predictors of comorbidity onset (p = .004 and p = .001, respectively). Atomoxetine was preferred more often as a first-line treatment in females, while psychostimulants were used at higher doses in males (p = .035 and p = .050, respectively). Conclusions More attention is needed for females with ADHD. Oppositionality, impulsivity, emotional lability, ADHD severity, age, and SLD appear to be important for the onset of internalizing and externalizing comorbidities.